Management of Insurers’ Investment - Solvency II Implication - Wasiak, Włodzimierz (Studia Oeconomica Posnaniensia, 2018)
The aim of the study is to identify (with a high degree of generalization) the most important elements, which asset managers must take into account when making investment decisions on the assumption, that Solvency Capital Requirement are calculated and based on the standard formula, not the internal model. The study contains practical tips of how to limit the Solvency Capital Requirement which is based on the most common market financial instruments.